Establishing a core outcome measure for life participation in patients receiving peritoneal dialysis: A Standardised Outcomes in Nephrology–Peritoneal Dialysis consensus workshop report. Issue 6 (November 2022) - Cheetham, Melissa S; Wilkie, Martin; Loud, Fiona; Manera, Karine E; Ju, Angela; Figueiredo, Ana; Farragher, Janine; Hurst, Helen; Jassal, Sarbjit V; Mehrotra, Rajnish; Morton, Rachael L; Schwartz, Daniel; et al.
Background: Life participation is an outcome of critical importance to patients receiving peritoneal dialysis (PD). However, there is no widely accepted or validated tool for measuring life participation in patients receiving PD. Methods: Online consensus workshop to identify the essential characteristics of life participation as a core outcome, with the goal of establishing a patient-reported outcome measure for use in all trials in patients receiving PD. Thematic analysis of transcripts was performed. Results: Fifty-six participants, including 17 patients and caregivers, from 15 countries convened via online videoconference. Four themes were identified: reconfiguring expectations of daily living (accepting day-to-day fluctuation as the norm, shifting thresholds of acceptability, preserving gains in flexibility and freedom), ensuring broad applicability and interpretability (establishing cross-cultural relevance, incorporating valued activities, distinguishing unmodifiable barriers to life participation), capturing transitions between modalities and how they affect life participation (responsive to trajectory towards stable, reflecting changes with dialysis transitions) and maximising feasibility of implementation (reducing completion burden, administrable with ease and flexibility). Conclusions: There is a need for a validated, generalisable outcome measure for life participation in patients receiving PD. Feasibility, including length of time to complete and flexible mode of delivery, are important to allow implementation in all trials that include patients receiving PD. Graphical Abstract This is a visual representation of the abstract.